Network Expansions in Kerala State Rtc - P, Parthiban; Verghese, Vincy (International Research Journal of Multidisciplinary Technovation, 2019)
The cornerstone of any great public transport organization is its expanding network of operations catering the passengers’ demand of all classes of people. Kerala State Road Transport Corporation is in the process of bringing inefficiency within the area of operations in the state and the expansion of its networks is an integral part of achieving it. The network expansion occurs with the introduction of new routes that can coordinate with the existing ones, thereby meeting the passenger demand of the state. The project attempts to recognize the new routes, feasible for the operations of Kerala State Road Transport Corporation. The project extension will be based on the current operational routes of Kerala State Road Transport Corporation and the distinguished potential routes. The project will consist of distinguishing the high-density private routes thereby analysing the nature of commuting in respect of age group, time and purpose of travel. The existing operational concerns will be addressed thereby identifying the routes of operation. Based on the demand assessment, bus operations and the conceivable revenue generations will be articulated